Matrices matemáticas con TIC : preparación a la educación superior - Arévalo Arévalo, Cristian Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: The solution of mathematical problems by means of matrix is an important and very useful topic to face the contents of most professional careers. It is known that the results achieved in the first stages of professional training, the competences in mathematical problem solving and the use of ICT are related to the quality of the previous knowledge acquired at the basic and secondary education levels. With the above, it is possible to assure that knowing the subject of mathematical matrix results in an advantage to face the first levels of professional training in the area of calculus. For this reason, the purpose of this study was to determine the incidence of didactic strategies in the learning process of some students with the help of mathematical matrix and their development with the help of ICT. From the results obtained, it is worth noting that it is important that students feel motivated and interested in the contents of the mathematics area and that for this to happen it is essential that teachers are concerned about implementing appropriate strategies and that they take advantage of the technological tools available to them.